Mestara: Penguatan Potensi Perempuan Muda melalui Women Support Women-Based Program - Qomaro, Galuh Widitya (Proceedings of Annual Conference on Community Engagement, 2022)
The women's empowerment program by Mestara aims to empower and improve the lives of young women in rural areas in Indonesia. The program promotes awareness of sexual health and economic potential to help women gain control over their own well-being. This program was initiated by women in order to increase the dignity of women. The ongoing Mestara Berdaya program has helped 60 young women in Geger Bojonegoro to recognize their potential and 15 of them master basic sewing techniques.